Comparison of clinical course of Acute Biliary and Non-Biliary Pancreatitis - Bhattarai, Abhishek; Devkota, Pragya; Kandel, Bishu Prasad; Ghimire, Bikal; Kansakar, Prasan Bir Singh; Bhandari, Ramesh Singh; Tamrakar, Kishor Kumar; Lakhey, Palaswan Joshi; Mishra, Parshuram; Singh, Yogendra Prasad; et al. (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Incidence of acute pancreatitis (AP) varies in different parts of the world. The published data are mainly based on retrospective analysis of hospital admissions, which show that there are considerable geographical differences in the incidence rate. There are also regional divergences with regard to the etiology, and its impact on morbidity and mortality. Therefore, we compare the clinical course of acute biliary and non-biliary pancreatitis at the Tribhuvan University Teaching Hospital (TUTH) as well as we compare the morbidity and mortality and duration of hospital stay in these groups. Methods: This prospective study included the patients with a diagnosis of AP over a period of one year. Eighty-five patients with the diagnosis of AP were included in the study. Revised Atlanta classification system (2012) was used to diagnose and define the severity of disease. The occurrence of local and systemic complications, median duration of hospital stay and mortality in AP was studied. Results: Among 85 patients, 34 patients were females and 51 were males. Among them, 46 patients belonged to the biliary group and 39 belonged to the non-biliary group. Alcohol intake was the major etiology in the non-biliary group (n = 26) and all of them were male. The majority of the gallstone induced AP patients were female (n = 29). Twenty-nine patients developed severe acute pancreatitis (SAP: 16 in biliary and 13 patients in non-biliary group). Complications were mostly seen in SAP. The acute fluid collection was the most common local complication (15 patients in biliary and 15 patients in non-biliary group, p > 0.05) and respiratory failure was the most common systemic complication (18 patients in biliary and 16 patients in non-biliary group, p > 0.05) in both groups. Three patients in biliary group and four patients in non-biliary group died due to multi-organ failure (p > 0.05). There was no statistical significant difference in the median duration of hospital stay in these groups. Conclusion: Though pathogenesis vary for different etiologies, once the disease process has started, local complications, systemic complications, duration of hospital stay and mortality in AP depends on the severity of the disease irrespective of the etiology.